EP263 Laparoscopic surgery improves short- and medium-term outcomes of nerve-sparing radical hysterectomy: a propensity-matched analysis with open abdominal procedures. (1st November 2019) - Bogani, G; Chiappa, V; Ditto, A; Raspagliesi, F
Abstract : Introduction/Background: To investigate the impact of laparoscopic surgery on short- and medium-term outcomes of cervical cancer patients undergoing nerve-sparing radical hysterectomy. Methodology: Data of consecutive patients affected by locally-advaced cervcial cancer who had neoadjuvant chemotherapy followed by laparoscopic nerve-sparing radical hysterectomy were matched 1:1 with an historical cohort of patients undergoing neoadjuvant chemotherapy followed by open radical hysterectomy, using propensity matching algorithm. Results: Thirty-five patients' pairs (70 patients: 35 undergoing laparoscopic vs. 35 undergoing open abdominal nerve-sparing radical hysterectomy) were included. Demographic and baseline oncologic characteristics were balanced between groups. Patients undergoing laparoscopic surgery had similar operative time than patients undergoing open abdominal procedures (249 [±91.5] vs. 223 [±65.0] minutes; p=0.066). Laparoscopic approach correlated with lower blood loss (30.5 [±11.0] vs. 190 [90.4] mL; p<0.001) and shorter hospital stay (3.2 [±1.2] vs. 5.4 [2.0] days; p=0.023). Patients undergoing laparoscopy experienced a lower 30-day pelvic floor dysfunction rate than patients having open surgery (p=0.024). Moreover, they experienced shorter recovery of bladder function than patients having open procedures (median, 7 vs. 9 days; p=0.004, log-rank test). After a median follow-up of 51.7 and 14.7 months for open abdominal and minimally invasive procedures, disease-free (p=0.617) and overall (p=0.814) survivals were similar between groups. Using multivariate model, we observed that the adoption of laparoscopic approach did not impact on disease-free (HR: 1.32 (95%CI: 0.58, 3.01); p=0.50) and overall (HR: 1.26 (95%CI: 0.41, 3.81); p=0.67) survivals. Conclusion: Laparoscopic nerve sparing radical hysterectomy resulted in improved short-term outcomes, without impacting on medium-term oncologic outcomes. Further prospective trials are needed to assess long-term outcomes of patients having minimally invasive surgery. Disclosure: Nothing to disclose.